Conference Report from the Scientific and Professional Conference “Islamic Culture and Tradition in Orasje from the Middle of the 19th Century to the Present”, Majlis of the Islamic Community of Orašje, Institute for Social and Religious Research Tuzla, Muftijstvo Tuzla, Orasje, 7/12/2022. - Mirsad Arnautalić (Historijski pogledi, 2023)
Conference Report: Izvještaj sa Naučno-stručne konferencije “Islamska kultura i tradicija u Orašju od sredine 19. stoljeća do danas”, Medžlis islamske zajednice Orašje, Institut za društvena i religijska istraživanje Tuzla, Muftijstvo tuzlansko, Orašje, 7. 12. 2022. godine // Conference Report from the Scientific and Professional Conference “Islamic Culture and Tradition in Orasje from the Middle of the 19th Century to the Present”, Majlis of the Islamic Community of Orašje, Institute for Social and Religious Research Tuzla, Muftijstvo Tuzla, Orasje, 7/12/2022.